Role of official editors in proving ownership - Al Barakati, Ahmed Abdullah Ali (Journal of Economic, Administrative and Legal Sciences, 2018)
The study dealt with the issue of consumer protection against misinformation in the light of the Saudi and Emirati laws. The study has clarified that the commercial advertisements are positively important, and that the offer to addressed the public through advertisements is also positive. The commercial contract is made via to the advertisements. The commercial advertisements are one of the ways which is making the contract between the party and the consumers. The study has discussed and clarified the mechanisms which can protect the consumer from misleading advertising. And also talked about the responsibility of the advertiser in clearing commercial advertising, and the issues of civil and criminal responsibility of misleading advertising. Then the study detailed the issue of consumer protection from misleading advertising in the Saudi system in general, where the system defined the advertisements as anyone who advertises or promotes the product using various means of advertising. And also the study indicates that there is no specific definition on what accurately is applying in this regard in the Saudi system, or definition of the person of the advertiser. This is what is taken as it opens the way for advertisers to exploit this in misleading consumers within the system. The first was clearly and unambiguously, For example, which is considered misleading if it affects the average consumer, who has a moderate state of caution and intelligence. The study also examined the issue of consumer protection against misleading advertising in UAE law. The UAE, through the consumer protection law and its executive regulations, detailed the provisions related to the commercial advertisement, and the penalties imposed on misleading advertising.
Keywords: Commercial; Advertisements; Saudi System; UAE Law